Base editing HbS to HbG-Makassar improves hemoglobin function supporting its use in sickle cell disease - Zachary Kostamo; Manuel A. Ortega; Chavonna Xu; Patricia R. Feliciano; Elizabeth Budak; Daisy Lam; Valerie Winton; Rebecca Jenkins; Archita Venugopal; Margaret Zhang; John Jamieson; Brent Coisman; et al. (Nature Communications)
Abstract Adenine base editing can convert sickle hemoglobin (HbS, βΕ6V) to G-Makassar hemoglobin (HbG, βE6A), a naturally occurring variant that is clinically asymptomatic. However, the quality and functionality of purified HbG and of mature HbGG and HbGS red blood cells (RBC) has not been assessed. Here, we develop a mouse model to characterize HbG. Purified HbG appears normal and does not polymerize under hypoxia. The topology of the hemoglobin fold with the βΕ6Α mutation is similar to HbA in the oxy and deoxy states. However, RBC containing HbGS are dehydrated, showing altered function and increased sickling under hypoxia. Blood counts and mitochondrial retention measures place HbGS RBCs as intermediate in severity between HbAS and HbSS, while organ function is comparable to HbAS. HbGG resembles HbAA for most metrics. Our results highlight the importance of functionally assessing the mature red cell environment when evaluating novel gene editing strategies for hematologic disorders.